COVID-19 and the right to health in Africa
1 online resource (xiv, 388 pages).
Keywords: This collection draws upon a range of thematic and regional case studies and uses the right to health as a normative framework to explore the devastating impact of the COVID-19 pandemic in Africa. Drawing lessons from across the continent, the book discusses the challenges faced by African states seeking to ensure the availability, accessibility, and quality of health care in the context of the COVID-19 pandemic. In particular, the volume explores the impact of the pandemic on the right to health of vulnerable and marginalized groups, such as women, children, elderly persons with disabilities, refugees and asylum seekers, and people from disadvantaged communities. Due to the poor funding of the healthcare systems, access to health-related services was limited to these groups in many African countries, thereby leading to avoidable COVID-19-related deaths through shortages of vital supplies, including diagnostic tests, ventilators, and oxygen cylinders. Chapters in the volume also explore the contentious issues of vaccine mandates, equity, resource allocation, and the rights of healthcare providers during the pandemic. This collection will be of interest to students of public health, human rights, and the social sciences, as well as to academics and policymakers with an interest in the nexus between the COVID-19 pandemic and public health policy in Africa.